2019
DOI: 10.4314/as.v18i1.9
|View full text |Cite
|
Sign up to set email alerts
|

Termite activities and surface characteristics of coastal plain sands

Abstract: This study evaluated the effect of mound building termites on the increase in the quantity of fine particles of the dimension of clay on the surface of coastal plain sands of south-eastern Nigeria. Six termite mounds were selected in different locations, destroyed completely and sampled in three replications. Surface and subsurface soils were sampled within the periphery of the termite mounds in similar replications as the mounds. Samples were processed and analyzed in the laboratory. Data were analysed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
2
2
0
Order By: Relevance
“…Based on the OC-to-clay index stated by Merante et al [56], the high to moderate OC content in pedon M02 could also be associated with a complex OC with clay content, which could lead to C stabilization. Regarding the OC levels of the mounds, the result is consistent with the observation of Obi et al [57] and demonstrates topographic efects. In addition to the high mineralization rate in a semiarid area, the fact that fungus-growing termites mineralize about 20% of the total OC [11] probably results in a low OC content.…”
Section: Chemical Properties Of Termite-mediated Soils Soil Ph (1 : 2...supporting
confidence: 91%
See 1 more Smart Citation
“…Based on the OC-to-clay index stated by Merante et al [56], the high to moderate OC content in pedon M02 could also be associated with a complex OC with clay content, which could lead to C stabilization. Regarding the OC levels of the mounds, the result is consistent with the observation of Obi et al [57] and demonstrates topographic efects. In addition to the high mineralization rate in a semiarid area, the fact that fungus-growing termites mineralize about 20% of the total OC [11] probably results in a low OC content.…”
Section: Chemical Properties Of Termite-mediated Soils Soil Ph (1 : 2...supporting
confidence: 91%
“…While termite pedoturbation did not afect the Na + and Mg 2+ across the toposequences, their efects were evident for Ca 2+ at all locations and K + at the foot slope and bottom slope positions. In support of this study, Obi et al [57] also considered Ca 2+ , Mg 2+ , and K + as indicators of pedoturbation.…”
Section: Chemical Properties Of Termite-mediated Soils Soil Ph (1 : 2...supporting
confidence: 68%
“…the area where the termites build their mound contribute to a greater extend in determining the fertility of the termite mound soil (Bonanomi andMazzoleni, 2005, Passioura, 2002). Homogenization of the constituent of the mound materials and redistribution to the surrounding environments through washing away of the mound soils also plays a part in the uniform distribution of materials around the mound which might also affect the growth of the plant (Obi et al, 2019). Termites mound soil can serve as amendments most especially to subsistence farmers who could not afford fertilizers to supplement the nutrient deficient soils of their farm lands ( Yanggen et al, 1998;Chisanga et al, 2020).…”
Section: Analysis Of Plants Grown On Different Layers Of the Termite ...mentioning
confidence: 99%
“…While -Zörb et al (2014) reported some of the symptoms of potassium deficiencies in plants to include brown spots on leaf surface or edge of the leaves and chlorosis at the tip of the older leaves. Smil (1999) reported that symptoms could be remedified by applying sufficient potassium fertilizers to the farmland Obi et al (2019) revealed that there is no difference in termite mounds soil and that of the surface soil in available phosphorus, exchangeable sodium and potassium, effective cation exchange capacity, fine sand and silt where they suggest that the similarities were as a result of uniform distribution through erosion and redistribution of the mound material around the mound that were studied. Similarly, Tilahun et al (2021) reported the availability of nutrients in termite mound soils and its efficacy as soil amendment.…”
Section: Introductionmentioning
confidence: 99%